Pathological study of non-neoplastic skin lesions by punch biopsy - Veldurthy, Vijay Sreedhar; Shanmugam, Chandrakumar; Sudhir, Nelluri; Sirisha, Ommini; Motupalli, Charan Paul; Rao, Narsing; Reddy, Siva Ram; Rao, Narasimha (International Journal of Research in Medical Sciences, 2017)
Background: Accurate diagnosis of skin disorders is of utmost importance as treatment is varied for different skin disorders presenting with the similar clinical lesions. Thus biopsy becomes inevitable in various skin disorders to confirm diagnosis and initiate treatment. The present study was to analyse the age and sex distribution of dermatological disorders presenting to Bhaskar Medical College & Hospital (tertiary care centre), Telangana and assess their histo-pathological profile. The objective was to analyse the histo-pathological profile of skin disorders presenting to the Dermatology department of the hospital, determine the age and sex distribution of various skin diseases and to classify the most common disorders into their subtypes and thus assess the most common subtypes prevalent in the surrounding community. Methods: This was a prospective study carried out at the department of Pathology and department of Dermatology, Bhaskar Medical College & Hospital for a period of three years. Necessary clinical details were obtained in a proforma, punch biopsy taken and sent to the histopathology section for final report. Formalin fixed, paraffin embedded sections were prepared & slides were routinely stained with H & E and special stains applied wherever necessary. Data obtained was tabulated and analysed. Results: Total number of cases analysed were 92. The age group of 21-30 years constituted 31.5% of the total cases. There was a male predominance. Hyperpigmented patch/plaque was the most common clinical lesion (36.9%). Lichenoid lesions was the most common histopathological diagnosis reported (26%) followed by Hansen’s disease(23.9%). Lichen planus was the most common histopathological subtype of lichenoid lesion s(58.3%).